On the determinants of external imbalances and net international portfolio flows: a global perspective - Roberto A. De Santis; Melanie Lührmann (European Central Bank (ECB), 2006)
In a panel covering a large number of countries from 1970 to 2003, we show that net portfolio flows play an important role in correcting external imbalances, since they are driven by common determinants represented by countries' demographic profiles, the quality of institutions, monetary aggregates and initial net financial asset positions. Population ageing causes current account deficits, net equity inflows and net outflows in debt instruments. A higher money to GDP ratio – associated with lower interest rates – favours international investments in domestic stocks to the detriment of the less attractive domestic bonds. Additionally, current account balances are driven negatively by real GDP growth, losses in competitiveness and increases in the quality of the institutions; net equity flows are driven positively by the quality of the institutions and negatively by per capita income; while net flows in debt instruments are driven by long-term interest rate differentials and deviations from the UIP.
Keywords: F21; F32; F41; O16; 330; Current accounts; net portfolio flows; panel regressions; Leistungsbilanz; Portfolio-Investition; Welt